Budget Transparency in Indonesia Case: Implications for Economic Performance and Growth - Donny Teguh Santoso Junias; Made Denny Oktariyana (CV. Sakura Digital Nusantara, 2026)
Purpose – This study investigates the role of budget transparency in enhancing economic performance and growth in Indonesia. It specifically examines how informational openness in public financial management influences government accountability and economic outcomes, measured by Gross Domestic Product and per capita income growth. Design/methodology/approach – This research employs a quantitative approach using pooled statistical data. The analysis integrates the International Budget Partnership’s Open Budget Index 2006-2024 with national economic indicators obtained from the Central Bureau of Statistics and the Ministry of Finance of the Republic of Indonesia. The constructs were analyzed using multiple regression analysis. Finding/Results – The results demonstrate that greater budget transparency has a positive and significant impact on economic performance and economic growth. Transparency is identified as an essential mechanism for optimizing resource allocation and fostering fiscal responsibility. Originality/Value – This study contributes to the theoretical frameworks of Contingent Approach, Agency Theory, Governance Theory, and Economic Growth Theory by providing empirical evidence from the Indonesian context. It underscores that budget transparency is not merely an administrative requirement but a critical, strategic driver of sustainable economic development.